NB/TA AND ZR/HF IN OCEAN ISLAND BASALTS - IMPLICATIONS FOR CRUST-MANTLE DIFFERENTIATION AND THE FATE OF NIOBIUM - Pfänder J.A.; Münker C.; Mezger K.; Stracke A. (My University, 2007)
Variations of high-field strength element (HFSE) ratios in terrestrial reservoirs, in particular Zr/Hf and Nb/Ta, are critical for understanding crust-mantle differentiation. Growing experimental and observational evidence shows that these ratios are fractionated during magmatic processes, despite their very similar geochemical characteristics. Here we present new high-precision Nb, Ta, Zr, Hf and Lu measurements for a variety of ocean island basalts determined by isotope dilution MC-ICPMS together with Hf isotope compositions in order to constrain OIB source characteristics and HFSE fractionation during mantle melting and crystal fractionation. Observed variations in Zr/Hf are larger than expected from fractional crystallisation alone. Partial melting of garnet and/or spinel peridotite assemblages can produce the observed range in Zr/Hf and Nb/Ta ratios, but require the presence of grossular-rich garnet, i.e. of recycled eclogite or garnet pyroxenite in the source of OIBs. This is consistent with Lu/Hf ratios that are lower in OIBs than expected from partial melting of pure garnet peridotite sources. Nb/Ta ratios in terrestrial reservoirs can be used to place constraints on crust-mantle differentiation and mantle evolution since the Archean. The average Nb/Ta in the OIB source region (15.9 ± 0.6 (1σ)) is identical to values observed in many MORB suites, but higher than the ratio of the bulk silicate Earth (~ 14) and the estimate for the continental crust (~ 12-13). Despite the inferred presence of recycled eclogite in OIB sources, which had previously been postulated to be a potential reservoir with superchondritic Nb/Ta ratios, their Nb/Ta ratios are invariably subchondritic and therefore provide no evidence for the existence of a silicate reservoir with superchondritic Nb/Ta in the Earth's mantle, and also exclude significant contributions from core material with superchondritic Nb/Ta ratios. The complementary Nb/Ta ratios in the Earth's crust and mantle with respect to bulk silicate Earth can be explained by partial melting of amphibolite bearing slabs with bulk DNb/Ta > 1 during crust-mantle differentiation. As melting of subducted amphibolites was probably most intense during the Archean, major portions of the continental crust may have formed early in Earth's history. Such a model is consistent with Nb/Ta ratios in Archean rocks and with 142Nd and 176Hf/177Hf evidence for early Earth differentiation. © 2007 Elsevier B.V. All rights reserved.
Keywords: CRUSTAL RECYCLING; HFSE; MANTLE EVOLUTION; NB/TA; OIB; ZR/HF; Archean; Precambrian::Archean; Докембрий::Архей